Orthognathic surgery in a patient with sickle cell disease: A case report and review of literature - Hussain Albannai; Abdulla Hanfesh; Yousif Al Nasrallah (Oral and Maxillofacial Surgery Cases)
Sickle cell disease is a genetic hemoglobinopathy that has the potential to affect any organ of the body. Patients with sickle disease have high morbidity and mortality creating safety concerns among patients and physicians about surgery in this subset of population. Factors that predispose SCD patient to complications are divided into patient-related and surgery-related factors. Patient factors associated with increased complication rate include the type and severity of SCD.Orthognathic surgery involves osteotomies, major movement of upper or lower jaw that, although safe, have the potential of list of complications in healthy individuals. Therefore, complications are expected to be higher in SCD population. This complicates the decision of surgery and mandates careful perioperative management.